1998
DOI: 10.1016/s0002-9440(10)65698-2
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Receptor Knockout Mice Are Protected from the Fibroproliferative Effects of Inhaled Asbestos Fibers

Abstract: We have demonstrated that C57BL/6-129 hybrid mice with genes for both the 55kd and 75kd receptors for TNF-alpha knocked out (TNF-alphaRKO) fail to develop fibroproliferative lesions after asbestos exposure. There is good evidence that TNF-alpha plays a major role in mediating interstitial pulmonary fibrosis. Our findings support this view and we present here new data obtained by in situ hybridization showing that expression of the genes coding for transforming growth factor alpha (TGF-alpha) and platelet-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
91
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 29 publications
(38 reference statements)
8
91
0
3
Order By: Relevance
“…As a consequence, a large amount of extracellular matrix (ECM) is produced, and the lungs reach a state of fibrosis and asbestosis [6,7]. In particular, TNF-a plays a role in production of transforming growth factor-beta (TGF)-b, which induces production of ECM, and previous studies have demonstrated that TNF-a receptor knockout mice showed decreases in production of TGF-b and accumulation of ECM after exposure to asbestos [6,8]. Moreover, asbestos exposure causes apoptosis of lung epithelial cells, mesothelial cells, and AM [9], and it has been reported that intratracheal instillation with apoptotic cells of macrophages induces increased production of TGF-b and fibrosis of the lungs [10].…”
Section: Role Of Alveolar Macrophages In Lung Inflammation Caused By mentioning
confidence: 99%
“…As a consequence, a large amount of extracellular matrix (ECM) is produced, and the lungs reach a state of fibrosis and asbestosis [6,7]. In particular, TNF-a plays a role in production of transforming growth factor-beta (TGF)-b, which induces production of ECM, and previous studies have demonstrated that TNF-a receptor knockout mice showed decreases in production of TGF-b and accumulation of ECM after exposure to asbestos [6,8]. Moreover, asbestos exposure causes apoptosis of lung epithelial cells, mesothelial cells, and AM [9], and it has been reported that intratracheal instillation with apoptotic cells of macrophages induces increased production of TGF-b and fibrosis of the lungs [10].…”
Section: Role Of Alveolar Macrophages In Lung Inflammation Caused By mentioning
confidence: 99%
“…In as much as chrysotile is the most commonly used form of asbestos worldwide, 6 we typically use this variety of fiber for both in vitro and in vivo studies. 7 We have primarily used chrysotile in the studies reported here and have compared these findings with crocidolite asbestos, a fiber with iron as a component of its chemical formula. 6 A number of cytokines are thought to be significant contributors in the development of human interstitial fibrosis and in models of pulmonary fibrogenesis.…”
mentioning
confidence: 99%
“…6 A number of cytokines are thought to be significant contributors in the development of human interstitial fibrosis and in models of pulmonary fibrogenesis. For example, it has been demonstrated that inhalation of asbestos enhances tumor necrosis factor-a (TNF-a), 7 transforming growth factor-a (TGF-a), 8 platelet-derived growth factor (PDGF) isoforms, 9 transforming growth factor beta (TGF-b), 10,11 as well as fibronectin expression at sites of fiber deposition, 10 correlating with elevated levels of cellular proliferation, 9 and extracellular matrix (ECM) deposition in both rats 10,12 and mice. 11 Of these factors, TGF-b 1 is the most potent in upregulating genes involved in collagen and fibronectin biosynthesis.…”
mentioning
confidence: 99%
“…In contrast to experiments with TNF␣-transgenic mice, these studies demonstrated uniformly that inhibition of signaling via TNFRI and TNFRII prevents the development of fibrosis. For instance, TNFRI Ϫ/Ϫ /II -/-mice were protected from experimental pulmonary fibrosis induced by silica, asbestos, and bleomycin (52)(53)(54). In contrast to WT mice, TNFRI Ϫ/Ϫ /II -/-mice did not demonstrate significant inflammation or increased proliferation in the lungs after exposure to profibrotic agents, the induction of TNF␣ was diminished, and there was no increased deposition of ECM.…”
Section: Tnf␣ In Fibrotic Diseases 2231mentioning
confidence: 95%